8(m+3)=48

Simple and best practice solution for 8(m+3)=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(m+3)=48 equation:


Simplifying
8(m + 3) = 48

Reorder the terms:
8(3 + m) = 48
(3 * 8 + m * 8) = 48
(24 + 8m) = 48

Solving
24 + 8m = 48

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 8m = 48 + -24

Combine like terms: 24 + -24 = 0
0 + 8m = 48 + -24
8m = 48 + -24

Combine like terms: 48 + -24 = 24
8m = 24

Divide each side by '8'.
m = 3

Simplifying
m = 3

See similar equations:

| 6c-9=36c+20 | | y=60000+1 | | 13x+10=69 | | 5u-8v+9(2u-3v)-4(2v-5u)= | | 3x^4+5x^3-x^2-5x-2=0 | | 130-25t=15 | | (4x-3)2+7=39 | | x*3+x*2-12=0 | | 5x^2+20x-30=15 | | 23x+6-27x=2-8 | | 5c+2=5c+4 | | z=10-2x^2 | | f(-5)=(x^2)-5x+7 | | Ax+3=6x+b | | 3x^2+2x+10=900 | | 4x-8=12(4+3x) | | -19(5c-8)-12c= | | (4x-12)(x+7)=0 | | p=140-0.5x | | -6=2x-1x | | 6x^2+22x-18=0 | | y=-a-x | | Ln(x)=24 | | 6x^2+22-18=0 | | 6a=6a+12 | | x(x-4)(x+14)=0 | | ax+1=bx-y | | P=80x-.4x^2-200 | | .8x-4=2x-3 | | 21x-5x=32 | | 9x+1=6x+6 | | 32-6x=14-9x |

Equations solver categories